2006
DOI: 10.1029/2006ja011630
|View full text |Cite
|
Sign up to set email alerts
|

On the coupling of layer instabilities in the nighttime midlatitude ionosphere

Abstract: [1] There are two plasma-structuring mechanisms that are known to operate at night in the midlatitude ionosphere, the Perkins instability (Perkins, 1973) in the F region, and the more recently discovered sporadic-E layer (E s L) instability (Cosgrove and Tsunoda, 2002) in the E region. Both are layer processes, whose coupled response has been shown to be more unstable than either by itself . Derived growth rates, however, were given only in terms of the most unstable mode; exactly how the individual growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 69 publications
3
83
0
Order By: Relevance
“…For example, they contribute to the formation of traveling ionospheric disturbances (TIDs) (e.g., Hines, 1960;Huang et al, 1994;Kirchengast et al, 1995;Vadas and Liu, 2009). In addition, it has been shown that there exists correlation between TIDs and sporadic E layers (Tsunoda, 2006), and the variations of sporadic E layers are influenced by both tides (e.g., Arras et al, 2009) and GWs (e.g., Woodman et al, 1991). Theoretical studies showing the importance of GWs in the T/I are presented by Vadas and Fritts (2005), Vadas and Fritts (2006), Vadas (2007), Fritts and Vadas (2008) and Yigit et al (2008).…”
Section: Q T Trinh Et Al: Satellite Observations Of Vertical Couplmentioning
confidence: 99%
“…For example, they contribute to the formation of traveling ionospheric disturbances (TIDs) (e.g., Hines, 1960;Huang et al, 1994;Kirchengast et al, 1995;Vadas and Liu, 2009). In addition, it has been shown that there exists correlation between TIDs and sporadic E layers (Tsunoda, 2006), and the variations of sporadic E layers are influenced by both tides (e.g., Arras et al, 2009) and GWs (e.g., Woodman et al, 1991). Theoretical studies showing the importance of GWs in the T/I are presented by Vadas and Fritts (2005), Vadas and Fritts (2006), Vadas (2007), Fritts and Vadas (2008) and Yigit et al (2008).…”
Section: Q T Trinh Et Al: Satellite Observations Of Vertical Couplmentioning
confidence: 99%
“…Huang et al (1994) identified gravity waves as a plausible explanation for driving MSTIDs in the bottomside F region, thus enhancing their growth rate. There is also a growing body of literature exploring E region coupling effects, through which the polarized electric field from a sporadic E layer maps efficiently to the F region, providing the seeding mechanism for MSTIDs (Tsunoda and Cosgrove, 2001;Cosgrove, 2004;Tsunoda, 2006;Yokoyama and Hysell, 2010).…”
Section: T M Duly Et Al: Climatology Of Mstid Occurrencesmentioning
confidence: 99%
“…4. Hysell and Burcham (2000); Hysell et al (2002);720 Y. S. Dimant and M. M. Oppenheim: Plasma cloud in ionosphere: effect of external field Yokoyama et al (2004) performed 2-D and 3-D numerical simulations of cloud polarization, current closure, and E-F region coupling, including the recently predicted sporadic-E instability Tsunoda, 2002b, 2004;Tsunoda et al, 2004;Tsunoda, 2006). These simulations give spatial distributions of the electric field but, being performed for particular cases only, provide no parameter dependencies as we will provide.…”
Section: Introductionmentioning
confidence: 99%